Captain Awesome gets a hole-in-one - Kirby, Stan (Kirby, Stan. Captain Awesome., 2014)
"When Eugene goes mini-golfing for Meredith Mooney's birthday party, he realizes he's actually an excellent mini-golfer! But Meredith realizes this too, and she starts to cheat so that she'll win. Will Eugene reveal her cheating ways?"--